Narrating Oneself, Narrating America: Gary Shteyngart's Little Failure: A Memoir (2014). - Bryla, Martyna Marika (Universidad de la Laguna, 2018)
This article analyses Gary Shteyngart’s Little Failure: A Memoir (2014) as a migrant’s tale providing a valuable insight into the search for the self on the threshold of several cultures. It argues that in addition to illuminating Shteyngart’s Russian-Jewish immigrant experience in America, the memoir reflects more universal concerns and uncertainties inherent in the process of acculturation while at the same time exposing pitfalls of multiculturalism.
ISBN: 978-84-15939-66-5
Keywords: Shteyngart, Gary - Crítica e interpretación; Gary Shteyngart; Migration; Multiculturalism; Identity